2008
DOI: 10.1002/pmic.200700507
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptidases in Nicotiana tabacum leaf intercellular fluid

Abstract: Peptidases in the extracellular space might affect the integrity of recombinant proteins expressed in, and secreted from, plant cells. To identify extracellular peptidases, we recovered the leaf intercellular fluid from Nicotiana tabacum plants by an infiltration-centrifugation method. The activity of various peptidases was detected by an in vitro assay in the presence of specific inhibitors, using BSA and human serum gamma-globulin as substrates. Peptidases were detected by 1- and 2-D zymography in a polyacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 104 publications
5
63
0
Order By: Relevance
“…of a previous MS analysis that identified some of the peptides corresponding to the SCPIII sequence in the leaf intercellular fluid (Delannoy et al, 2008) and our own MS results for the extracellular medium of BY-2 cells (data not shown). Moreover, western blotting using anti-His antibodies showed that NtSCP1-6-His was found in the leaf intercellular fluid of transgenic plant lines (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…of a previous MS analysis that identified some of the peptides corresponding to the SCPIII sequence in the leaf intercellular fluid (Delannoy et al, 2008) and our own MS results for the extracellular medium of BY-2 cells (data not shown). Moreover, western blotting using anti-His antibodies showed that NtSCP1-6-His was found in the leaf intercellular fluid of transgenic plant lines (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…cDNA Cloning of NtSCP1 and NtSCP2 from Tobacco Leaves Mass spectrometry (MS) analysis of tobacco leaf intercellular fluid resulted in the identification of tryptic fragments typical of SCPIII proteins (Delannoy et al, 2008). To clone the corresponding cDNA, degenerated SCPIII primers were designed based on the conserved upstream (MFYF/LF/LFESR) and downstream (VHDAGHMVPMDQPK) motifs of plant SCPIIIs in the MEROPS peptidase database (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations